A Coordinated Approach to Control Mechanical and Computing Resources in Mobile Robots - Shahsavari, Sajad; Haghbayan, Hashem; Miele, Antonio; Immonen, Eero; Plosila, Juha (Institute of Electrical and Electronics Engineers Inc., 2025)
Energy management of mechanical and cyber parts in mobile robots consists of two processes operating concurrently at runtime. Both the two processes can significantly improve the robots’ battery lifetime and further extend mission time. In each process, information on energy consumption of one of the two parts is captured and analyzed to manipulate various mechanical/computational actuators in a robot, such as motor speed and CPU voltage/frequency. In this paper, we show that considering management of mechanical and computational segments separately does not necessarily result in an energy-optimal solution due to their co-dependence; as a consequence, a runtime co-management scheme is required. We propose a proactive energy optimization methodology in which dynamically-trained internal models are utilized to predict the future energy consumption for the mechanical and computational parts of a mobile robot, and based on that, the optimal mechanical speed and CPU voltage/frequency are determined at runtime. The experimental results on a ground wheeled robot show up to 36.34% reduction in the overall energy consumption compared to the state-of-the-art methods.